Erythropoietin regulates the expression of dimeric form of acetylcholinesterase during differentiation of erythroblast. Issue 4 (23rd July 2018) - Xu, Miranda L.; Luk, Wilson K. W.; Bi, Cathy W. C.; Liu, Etta Y. L.; Wu, Kevin Q. Y.; Yao, Ping; Dong, Tina T. X.; Tsim, Karl W. K.
Abstract: Acetylcholinesterase (AChE; EC 3.1.1.7) is known to hydrolyze acetylcholine at cholinergic synapses. In mammalian erythrocyte, AChE exists as a dimer (G2 ) and is proposed to play role in erythropoiesis. To reveal the regulation of AChE during differentiation of erythroblast, erythroblast‐like cells (TF‐1) were induced to differentiate by application of erythropoietin (EPO). The expression of AChE was increased in parallel to the stages of differentiation. Application of EPO in cultured TF‐1 cells induced transcriptional activity of ACHE gene, as well as its protein product. This EPO‐induced event was in parallel with erythrocytic proteins, for example, α‐ and β‐globins. The EPO‐induced AChE expression was mediated by phosphorylations of Akt and GATA‐1; because the application of Akt kinase inhibitor blocked the gene activation. Erythroid transcription factor also known as GATA‐1, a downstream transcription factor of EPO signaling, was proposed here to account for regulation of AChE in TF‐1 cell. A binding sequence of GATA‐1 was identified in ACHE gene promoter, which was further confirmed by chromatin immunoprecipitation (ChIP) assay. Over‐expression of GATA‐1 in TF‐1 cultures induced AChE expression, as well as activity of ACHE promoter tagged with luciferase gene (pAChE‐Luc). The deletion of GATA‐1 sequence on the ACHE promoter, pAChEΔ GATA ‐1 ‐Luc, reduced the promoter activity during erythroblastic differentiation. On the contrary, the knock‐down of AChE in TF‐1 cultures could lead to a reduction in EPO‐induced expression of erythrocytic proteins. These findings indicated specific regulation of AChE during maturation of erythroblast, which provided an insight into elucidating possible mechanisms in regulating erythropoiesis. Abstract : In mammalian erythrocyte, acetylcholinesterase (AChE; EC 3.1.1.7) exists as a dimer (G2 ) and is proposed to play role in erythropoiesis. Here, erythroblast‐like cells (TF‐1) were induced to differentiate by application of erythropoietin (EPO). The expression of AChE was increased in parallel to the stages of differentiation. GATA‐1, a downstream transcription factor of EPO receptor, was proposed here to account for the regulation of AChE during erythropoiesis. In addition, the amount of AChE could modulate EPO‐mediated downstream gene expressions. These findings indicated specific regulation of AChE during maturation of erythroblast, which provided an insight in elucidating possible mechanisms in regulating erythropoiesis.